2023
DOI: 10.3389/fmicb.2023.1092360
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the gut microbiome of patients with type a aortic dissection

Abstract: ObjectiveTo investigate the characteristic changes in the gut microbiota of patients with type A aortic dissection (AAD) and provide a theoretical basis for future microbiome-oriented interventional studies.MethodsHigh-throughput 16S rDNA sequencing was performed on the stool samples of patients with and without (healthy control subjects) AAD. Using alpha and beta diversity analysis, we compared the gut microbiota composition of 20 patients with AAD and 20 healthy controls matched for gender, age, BMI, and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…While speci c evidence for this remains to be further explored, the potential role of the gut environment in the pathogenesis of PAH should not be overlooked. Despite con icting with animal experimental results, numerous microbiota sequencing studies on diverse disease populations have suggested that Firmicutes are bene cial bacteria for the human body, providing protective effects in various conditions such as aortic dissection, constipation, and primary aldosteronism (37)(38)(39). This suggests that the mechanisms of gut microbiota in animal models might signi cantly differ from humans.…”
Section: Sensitivity Analysis Resultsmentioning
confidence: 99%
“…While speci c evidence for this remains to be further explored, the potential role of the gut environment in the pathogenesis of PAH should not be overlooked. Despite con icting with animal experimental results, numerous microbiota sequencing studies on diverse disease populations have suggested that Firmicutes are bene cial bacteria for the human body, providing protective effects in various conditions such as aortic dissection, constipation, and primary aldosteronism (37)(38)(39). This suggests that the mechanisms of gut microbiota in animal models might signi cantly differ from humans.…”
Section: Sensitivity Analysis Resultsmentioning
confidence: 99%